Numerical problems, examples and objective questions in geotechnical engineering - Rao, A V Narasimha (Universities Press, 2013)
Numerical problems, examples and objective questions in geotechnical engineering / Rao, A V Narasimha. -- Kolkata: Universities Press, 2013 624.151 R215 No. of Copies : 1